1996
DOI: 10.1016/s0896-6273(00)80282-2
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of bcl-2 Results in Progressive Degeneration of Motoneurons, Sympathetic and Sensory Neurons during Early Postnatal Development

Abstract: Bcl-2 is a major regulator of programmed cell death, a critical process in shaping the developing nervous system. To assess whether Bcl-2 is involved in regulating neuronal survival and in mediating the neuroprotective action of neurotrophic factors, we generated Bcl-2-deficient mice. At birth, the number of facial motoneurons, sensory, and sympathetic neurons was not significantly changed, and axotomy-induced degeneration of facial motoneurons could still be prevented by brain-derived neurotrophic factor (BDN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
153
0
3

Year Published

1997
1997
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 255 publications
(165 citation statements)
references
References 85 publications
8
153
0
3
Order By: Relevance
“…Furthermore, a simple down-regulation of a single receptor cannot account for the change because postnatal RGCs fail to rapidly extend axons in response to all tested axon growth-promoting stimuli and substrates. The anti-apoptotic protein Bcl-2 was proposed as an intrinsic genetic switch that decreases axon growth rate by RGCs (Chen et al 1997), but Bcl-2 overexpression by purified RGCs in culture neither promotes axon growth nor enhances axon growth in response to neurotrophic signaling in vitro or in vivo (Goldberg et al 2002b), a result consistent with other findings (Greenlund et al 1995;Michaelidis et al 1996;Chierzi et al 1999;Goldberg and Barres 2000;Lodovichi et al 2001).…”
Section: What Molecular Changes Underlie the Developmental Loss In Rasupporting
confidence: 70%
“…Furthermore, a simple down-regulation of a single receptor cannot account for the change because postnatal RGCs fail to rapidly extend axons in response to all tested axon growth-promoting stimuli and substrates. The anti-apoptotic protein Bcl-2 was proposed as an intrinsic genetic switch that decreases axon growth rate by RGCs (Chen et al 1997), but Bcl-2 overexpression by purified RGCs in culture neither promotes axon growth nor enhances axon growth in response to neurotrophic signaling in vitro or in vivo (Goldberg et al 2002b), a result consistent with other findings (Greenlund et al 1995;Michaelidis et al 1996;Chierzi et al 1999;Goldberg and Barres 2000;Lodovichi et al 2001).…”
Section: What Molecular Changes Underlie the Developmental Loss In Rasupporting
confidence: 70%
“…Whether Beclin-1 can be manipulated to enhance the death of cancer cells expressing high amounts of Bcl-2 needs to be tested. It will be equally important to assess whether Beclin-1 disturbs the pro-survival effect of Bcl-2 in the nervous system, given that some classes of neurons depend on Bcl-2 for long-term survival (Michaelidis et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Homologous recombination (Table 2) revealed that Bcl-2 de®ciency is deleterious for certain cell types including lymphocytes (Nakayama et al, 1994), melanocytes (Yamamura et al, 1996), intestinal epithelial cells (Kamada et al, 1995), and some classes of neurons (Michaelidis et al, 1996). De®ciency of Bcl-X causes intrauterine death accompanied by massive loss of postmitotic immature neurons (Motoyama et al, 1995).…”
Section: Knock-out Studiesmentioning
confidence: 99%
“…Thus, a swap of a 23 aminoacid segment surrounding BH3 from Bax into Bcl-2 converted Bcl-2 from a death antagonist to a death agonist . (Nakayama et al, 1994) Lymphopenia (Nakayama et al, 1994) Accelerated G1-S cell cycle progression in T cells (Linette et al, 1996) Multicystic kidney, renal hypoplasia and renal failure (Nakayama et al, 1994;Sorenson et al, 1996) Gray hair due to accelerated loss of melanocytes (Yamamura et al, 1996) Decrease in the number of oocytes and primordial follicles (Ratts et al, 1995) Distorted small intestine with accelerated exfoliation of epithelial cells (Kamada et al, 1995) Degeneration of motoneurons, sympathetic, and sensory neurons during early postnatal development (Michaelidis et al, 1996) Enhanced susceptibility of cerebellar granule neurons to undergo apoptosis in vitro (Tanabe et al, 1997) Reduced axon growth rate in embryonic sensory neurons culutured in vitro (Hilton et al, 1997) Bcl-X Intrauterine death (E13) (Motoyama et al, 1995) Massive death of postmitotic immature neurons (Motoyama et al, 1995) Shortened life-span of immature lymphocytes (Motoyama et al, 1995) Enhanced death of serum-depleted telencephalic cells in vitro Bxl-w Sterility with progressive testicular degeneration, blockade in late spermiogenesis (Ross et al, 1998) (Deckwerth et al, 1996) More neurons in cervical ganglia and facial nuclei (Deckwerth et al, 1996) Prevents increased cell death of immature neurons in Bcl-X 7/7 mice (Shindler et al, 1997) Asymmetric receptor/ligand interactions among members of the Bcl-2 family Mutagenesis studies and NMR data revealed that intact BH1, BH2 and BH3 domains of the antagonists (Bcl-2, Bcl-X L ) are required for them to heterodimerize with the BH3 domain of Bak or Bax and to repress cell death (Sattler et al, 1997;Sedlak et al, 1995;Ying et al, 1994). It appears that the BH3 region forms and a helix which nestles into a crevice formed by the apposition of the BH1, BH2 and BH3 regions (Sattler et al, 1997).…”
Section: Bcl-2 Homology Regionsmentioning
confidence: 99%